Biomaterials for Tissue Engineering - Lee, Esther J. (2013)
Biomaterials serve as an integral component of tissue engineering. They are designed to provide architectural framework reminiscent of native extracellular matrix in order to encourage cell growth and eventual tissue regeneration. Bone and cartilage represent two distinct tissues with varying compositional and mechanical properties. Despite these differences, both meet at the osteochondral interface. This article presents an overview of current biomaterials employed in bone and cartilage applications, discusses some design considerations, and alludes to future prospects within this field of research.